Produção de café com certificação fair trade : uma alternativa para os produtores familiares - OLIVEIRA, Maria (2016)
Brazil is the world's largest coffee producer, and Minas Gerais, the state responsible for most of the coffee production in the country. In recent decades many changes have occurred in the production and consumption involving the coffee sector. Consumers and coffee buyers are more demanding about the social, environmental, economic and qualitative criteria; if the product is in compliance with labor laws, that is. Consequently, seeking to aggregate more value to their coffee production, farmers felt the need to find new methods to meet this new market niche. The Fair Trade certification has emerged as a good alternative to increase the benefit which was perceived by consumers of a differentiated coffee. Therefore, farmers associated with the Cooperative of Family Farmers from Poço Fundo were interviewed on five occasions in the meetings of the cooperative members. The study case showed that the income obtained from the marketing of the coffee with the Fair Trade certification led the farmers to better conditions to maintain a greater economic balance. Since they receive a fairer price for their coffee, the profits are reinvested in their rural properties. It is noteworthy that the participation in the Cooperative strengthened the farmers and gave them more tranquility and the feeling of being safe in their commercial transactions. It was observed that after the Fair Trade certification farmers have adopted sustainable practices which take into account the preservation of the environment.